Analysing the performance of lean manufacturing implementation with chronological execution of lean elements using spread sheet features: a case study. (3rd May 2019) - Sundar, R.; Balaji, A.N.; Kumar, R.M. Satheesh
Globalisation influences the manufacturing sector to practice the best manufacturing system to sustain in competing business environment. The outcome of this article elucidate the effect of transition from traditional manufacturing practice to lean manufacturing system in a paint brush company located in South India. The existing practice utilises push system where the large batches of raw material are routed from one operation to another along a production line. In this case study, a lean manufacturing system along with sequential implementation of lean elements such as value stream mapping, group technology, cellular manufacturing, U-line manufacturing, etc., is premeditated for reducing the cycle time to relax the Takt time and stabilising the production process. The implemented lean manufacturing system increases the productivity, reduces work-in-process and lead time. The performance measure of lean system such as bottleneck cycle time, production capacity, lead time and work-in-process inventory are evaluated by instant part transfer rate through spread sheet model.